Citizenship Behavior in the Workplace: An Exploration of Employee Motives - Kartika Nuradina; Aldinel Fikri; Diana Harding (Greenation Research & Yayasan Global Resarch National, 2024)
This research explores the role of motives in explaining individual involvement in organizational citizenship behavior (OCB). Three motives of citizen behavior were identified: prosocial values (PV), organizational concern (OC), and impression management (IM). Scales that measured these motives and other variables known to covary with OCB were correlated with 5 dimensions of OCB. Questionnaires were administered to 112 employees of Bandung City Municipal Office. Prosocial values exhibited the strongest association with individual-focused OCB, while organizational concern displayed the strongest link with organization-oriented OCB. Each motive independently contributed to explaining variance in OCB. The results emphasize the significance of motives in understanding OCB.